MENINGKATKAN KEMAHIRAN MOTORIK KASAR ANAK PRA SEKOLAH DI RA BAITUSSALAM CIMAHI MELALUI BERMAIN ANGKLUNG - siti yani aisyah; Fitriyani Solihat Solihat (CERIA (Cerdas Energik Responsif Inovatif Adaptif), 2019)
Abstract Learning activities in kindergartens was implemented through play activities. In carrying out the principle of learning in kindergarten there is a lot of learning strategies that can be use, one of them with "playing music". Play music including art activity for children kindergarten. When performing musical activities children can play several musical instruments as appropriate for kindergarten one IE tool music angklung. By playing the music will help the child express his feelings and creativity. For that team of researchers tried to find out the extent to which the strategy of playing the angklung can improve motor ability of abusive children. As for this research aims at: 1) to find out the capabilities of early motor rough early childhood. 2) know the planning play angklung. 3) know the process execution play angklung. 4) to find out the results of implementation of playing the angklung.The method used is the class action Research (PTK). This research was conducted in one of the kindergartens that are located in the village Setiamanah in the city of Cimahi. The research results obtained data about 1) process of learning by playing angklung can improve motor rough early childhood. 2) Impact strategy play angklung against rough motor ability of children. 3) factors that support and hinder the ability of motor rough early childhood with play angklung. The recommendations of this study are: 1) for the school, the need for the provision of the infrastructure used to support the motor ability of the rough early childhood. 2) For Educators to know the use of musical instruments in developing motor abilities angklung rough early childhood. 3) For instances of the Builder, as a reference about the strategy of playing the angklung motor ability in developing a rough early childhood. From the results of the study in this class Action was concluded that by playing angklung is a strategy that can be used to enhance the ability of a rough early childhood motor.